ответ: x = - 1.
Пошаговое объяснение:
Решим уравнение через дискриминант.
(- x - 4) * (3x + 3) = 0
- 3x² - 3x - 12x - 12 = 0
- 3x² - 15x - 12 = 0
D = b² - 4ac = (- 15)² - 4 * (- 3) * (- 12) = 225 - 144 = 81
x₁ = (- b - √D)/(2a) = (- (- 15) - √81)/(2 * (- 3)) = (15 - 9)/(- 6) = 6/(-6) = - 1
x₂ = (- b + √D)/(2a) = (- (- 15) + √81)/(2 * (-3)) = (15 + 9)/(- 6) = 24/(- 6) = - 4
- 1 > - 4 ⇒ в ответ записываем x = - 1.
Решим уравнение через разложение трёхчлена.
(- x - 4) * (3x + 3) = 0
[ - x - 4 = 0 x₁ = - 4
⇒
[ 3x + 3 = 0 x₂ = - 1
- 1 > - 4 ⇒ в ответ записываем x = - 1.
а) S = 2 1/3, б) сторона = 1/6
Пошаговое объяснение:
а)3 1/9 ×3/4 = 28/9 × 3/4 ( 7/3 ×1/1 ) = 7/3 или 2 1/3
б) 10 : 1 2/3 = 5/3 × 1/10 ( 1/3 × 1/2 ) = 1/6